Complexity of Knee Extensor Torque: Effect of Aging and Contraction Intensity - Fiogbé, Elie (2021)
ABSTRACT: Fiogbé, E, Vassimon-Barroso, V, Catai, AM, de Melo, RC, Quitério, RJ, Porta, A, and Takahashi, ACdM. Complexity of knee extensor torque: effect of aging and contraction intensity. J Strength Cond Res 35(4): 1050-1057, 2021-Assessing the knee extensors' torque complexity in older adults is relevant because these muscles are among the most involved in functional daily activities. This study aimed to investigate the effects of aging and isometric contraction intensity on knee extensor torque complexity. Eight young (24 ± 2.8 years) and 13 old adults (63 ± 2.8 years) performed 3 maximal (maximum voluntary contraction [MVC], duration = 10 seconds) and submaximal isometric contractions (SICs, targeted at 15, 30, and 40% of MVC, respectively) of knee extensors. Torque signals were sampled continuously, and the metrics of variability and complexity were calculated basing on the SIC torque data. The coefficient of variation (CV) was used to quantify the torque variability. The torque complexity was determined by calculating the corrected approximate entropy (CApEn) and sample entropy (SampEn) and its normalized versions (NCApEn and NSampEn). Young subjects produced greater isometric torque than older adults, and the CV was similar between both groups except at the highest force level (40% MVC) where young subjects' value was higher. The major novel finding of this investigation was that although the knee extensor torque complexity is reduced in older adults, its relationship with contraction intensity is similar to young subjects. This means that despite the age-related decrease of the interactions between the components of the neuromuscular system, the organization of force control remains preserved in older adults, at least up to just below the force midrange.